Depth Extent and Kinematics of Faulting in the Southern Tanganyika Rift, Africa. Issue 3 (2nd March 2019) - Lavayssière, Aude; Drooff, Connor; Ebinger, Cynthia; Gallacher, Ryan; Illsley‐Kemp, Finnigan; Oliva, Sarah J.; Keir, Derek
Abstract: Unusually deep earthquakes occur beneath rift segments with and without surface expressions of magmatism in the East African Rift system. The Tanganyika rift is part of the Western rift and has no surface evidence of magmatism. The TANG14 array was deployed in the southern Tanganyika rift, where earthquakes of magnitude up to 7.4 have occurred, to probe crust and upper mantle structure and evaluate fault kinematics. Four hundred seventy‐four earthquakes detected between June 2014 and September 2015 are located using a new regional velocity model. The precise locations, magnitudes, and source mechanisms of local and teleseismic earthquakes are used to determine seismogenic layer thickness, delineate active faults, evaluate regional extension direction, and evaluate kinematics of border faults. The active faults span more than 350 km with deep normal faults transecting the thick Bangweulu craton, indicating a wide plate boundary zone. The seismogenic layer thickness is 42 km, spanning the entire crust beneath the rift basins and their uplifted flanks. Earthquakes in the upper mantle are also detected. Deep earthquakes with steep nodal planes occur along subsurface projections of Tanganyika and Rukwa border faults, indicating that large offset (≥5 km) faults penetrate to the base of the crust, and are the current locus of strain. The focal mechanisms, continuous depth distribution, and correlation with mapped structures indicate that steep, deep border faults maintain a half‐graben morphology over at least 12 Myr of basin evolution. Fault scaling based on our results suggests that M > 7 earthquakes along Tanganyika border faults are possible. Key Points: Seismicity data are used to probe crust and upper mantle structure and to evaluate fault kinematics in the southern Tanganyika rift Brittle strain is localized to steep border faults that penetrate to 25‐ to 40‐km depth based on earthquake distribution and focal mechanisms Thick seismogenic layer and isolated swarms of upper mantle earthquakes indicate that M > 7 earthquakes are probable